Effect of nitroxide spin probes on the transport properties of Nafion membranes. Issue 41 (15th October 2018) - Überrück, Till; Neudert, Oliver; Kreuer, Klaus-Dieter; Blümich, Bernhard; Granwehr, Josef; Stapf, Siegfried; Han, Songi
Abstract : NMR, EPR, ODNP, conductivity, and hydration studies to examine Nafion water transport properties in the presence of TEMPO derived spin probes. Abstract : Nafion is the most common material used as a proton exchange membrane in fuel cells. Yet, details of the transport pathways for protons and water in the inner membrane are still under debate. Overhauser Dynamic Nuclear Polarization (ODNP) has proven to be a useful tool for probing hydration dynamics and interactions within 5–8 Å of protein and soft material surfaces. Recently it was suggested that ODNP can also be applied to analyze surface water dynamics along Nafion's inner membrane. Here we interrogate the viability of this method for Nafion by carrying out a series of measurements relying on 1 H nuclear magnetic resonance (NMR) relaxometry and diffusometry experiments with and without ODNP hyperpolarization, accompanied by other complementary characterization methods including small angle X-ray scattering (SAXS), thermal gravimetric analysis (TGA) of hydration, and proton conductivity by AC impedance spectroscopy. Our comprehensive study shows that commonly used paramagnetic spin probes—here, stable nitroxide radicals—for ODNP, as well as their diamagnetic analogues, reduce the inner membrane surface hydrophilicity, depending on the location and concentration of the spin probe. This heavily reduces the hydration of Nafion, hence increases the tortuosity of the inner membrane morphology and/or increases the activiation barrier for water transport, and consequently impedes water diffusion, transport, and proton conductivity.